Paperboy [compact disc, unabridged] - Vawter, Vince (Random House/Listening Library, 2013)
An 11-year-old boy living in Memphis in 1959 throws the meanest fastball in town, but talking is a whole different ball game. He can barely say a word without stuttering, not even his own name. So when he takes over his best friend's paper route for the month of July, he knows he'll be forced to communicate with the different customers, including a housewife who drinks too much and a retired merchant marine who seems to know just about everything.